A study of consumers preference of local or imported instant food product in Segamat town / Aznita Aishah Abdullah and Marlina Mohd Ali - Abdullah, Aznita Aishah; Ali, Marlina Mohd (2001)
Food, means 1 'substance taken in to maintain life and growth'. It is something that every living thing needs in order to live and gains energy. In the past, people hunt and eat anything that can be eaten to be able live. But nowadays, people are able and afford to choose their own food. Since we have entered into a new millennium, everyone and every thing needs to fast and quick that includes the food that they eat. What these people need is food for whatever time of day and for whatever time of their life. For example, children would want to eat food they really enjoy and taste good. Teens on the other hand, need to eat something that will give them energy for their active lives where they always rushing from one activity to another, so they tend to snack. They like lots of affordable enjoyment, with big potions and a succession of tastes and textures. As for young adults which active and sociable, they look out for something new and with new varieties and flavours combinations. And for homemakers, they need a quick and easy way to prepare specific dishes, where it can save time and effort So, a ready prepared food is what they need. Besides that when at work, a convenient and nourishing snack or beverage helps provide a welcome break and gives one energy to get through the day. People on the move want to be able to find good wherever they are and whatever time of day. So, what they need is instant food to suit today's busy lifestyle. For our research, we study with a comparison between instant local food and imported instant food. This study is to focus on the consumer's preference on local and imported instant food product in Segamat Town. To keep with the consumer's demand, more companies are producing easy and fast to prepare meals. This study is to find out which instant food product do consumers prefer; i.e. local or imported food. Among the variables looks upon are its price, quantises, brand name and the consumers taste. If we look at the price, local instant food product incurred lower cost that leads to cheaper prices rather than imported instant food product, which are more expensive. If looking at the quality of the product, imported instant food products are more of high quality compared to local instant food product. Another variable that can be considered is the brand name. Mostly people already set in their mind that imported food products are highly of standard. Furthermore, local consumers likely prefer imported food product more. In conducting this research, we firstly need to go through a problem definition process. The first step is the environmental context of the problem. In order to search more on the problem, we look at the past information and forecast that can be valuable in uncovering potential opportunities and problem. Then, we have to look at the buyers behaviour where we can trace in predicting the responses of buyers to specific actions by the marketer. This can be done in predicting consumption habit, consumption of product related categories, consumers in response to promotion and also the buyer's preference. For legal environment, we have to look at government law, trade agreements taxes and tariffs due to the imported products. The prices of the products also can be affected by economic condition of a county. The second step is the taste involve in problem definition. In this case, we did not use experience survey since we have to make comparison with a lot of brands. But then, we did a lot of data collection from the secondary data. It includes paper cuttings, On-line service, magazines and etc. The last step is the management decision problem and the research problem. Secondary data that can be gathered is the external secondary data which data gathered by sources outside the organization. Our external sources are from libraries where we find newspapers and magazines cuttings. Then, we also did focus group interviews. These interviews are free-flowing interviews with a small group of people. Most of these groups of people are housewives, students and working people. This type of interview method is the type that can discuss freely from brand to product itself. Furthermore, we did some observation using the observation method, in supermarkets. It is the systematic process of recording behavioural patterns of people, objects and occurrences without communicating with them. The researcher utilise the observation method of data collection witnesses and records information as events occur or compiles evidence from past event records. In this research, we are not doing research on one particular company only but on few food companies, which we are going to compare to find out which instant food products does the consumers prefer to buy and the reasons why. Here is some of the background information about some particular food companies.